Accurate local magnitude prediction for small to moderate earthquakes using rapid calculations of P-wave dominant period - Tjipto Prastowo; Berla Maghda Putri Mahanani; Latifatul Cholifah; La Ode Ngkoimani; La Ode Safiuddin (Journal of Science and Science Education, 2017)
This study examines mechanisms of rapid and accurate determination of local magnitude Mpd for small to moderate events that occurred in West Sulawesi and Central Sulawesi using direct procedures and calculations of the dominant period Td of P-waveforms. Secondary data were collected from Webdc3, comprising earthquake magnitudes in the regions of interest during 2008-2015 measured in MW. The study focuses on earthquake size estimates for local events as a parameter through simple evaluation of a linear equation relating Td to MW. For all the events considered, empirical formulas derived from the random data for estimating the size are, respectively, Mpd = (Td + 6.6799)/1.5199 for West Sulawesi and Mpd = (Td + 3.3648)/0.8464 for Central Sulawesi. Each was used to recalculate events in the two regions. The results were compared to the reference provided by the Global CMT catalog. The results are consistent with the reference having a standard deviation of up to 0.2, showing evidence of no significant difference in magnitude determination between the method proposed in the current study and that of the Global CMT. This suggests that rapid and accurate magnitude determination is best predicted by the empirical formula developed for each region in this study for future use of disaster risk reduction program.